2016
DOI: 10.21149/spm.v58i2.7789
|View full text |Cite
|
Sign up to set email alerts
|

Triage strategies in cervical cancer detection in Mexico: methods of the FRIDA Study

Abstract: Objective. This paper describes the study design and baseline characteristics of the study population, including the first 30 829 women who enrolled in the Forwarding Research for Improved Detection and Access for Cervical Cancer Screening and Triage (FRIDA Study). This is a large population based study that is evaluating the performance and cost-effectiveness of different triage strategies for high-risk HPV (hrHPV) positive women in Mexico. Materials and methods. The target population is more than 100 000 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 38 publications
1
38
0
3
Order By: Relevance
“…4,17 Preliminary results of a study in Mexico indicated that 27.0% of the hr-HPV positive women were referred to colposcopy due to a positive HPV 16/18 test and/or abnormal reflex cytology, with 31.6% ASCUS1, 53.6% HPV16/18 positive with a normal cytology result and 9.5% positive in both triage tests. 17 The high colposcopy referral rate of the cytology indicated its incompetency as a triage test. Compared with other studies, 18,19 our study identified most cases of CIN11 (Table 2) due to a high proportion of cytological abnormalities among the HPV positive women (48.4%) and this is likely also a consequence of excessive colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…4,17 Preliminary results of a study in Mexico indicated that 27.0% of the hr-HPV positive women were referred to colposcopy due to a positive HPV 16/18 test and/or abnormal reflex cytology, with 31.6% ASCUS1, 53.6% HPV16/18 positive with a normal cytology result and 9.5% positive in both triage tests. 17 The high colposcopy referral rate of the cytology indicated its incompetency as a triage test. Compared with other studies, 18,19 our study identified most cases of CIN11 (Table 2) due to a high proportion of cytological abnormalities among the HPV positive women (48.4%) and this is likely also a consequence of excessive colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…Mexico, in particular, continues to advance knowledge via a large scale study of colposcopy triage methods. 6 Mexico was the first Latin American country to adopt a two-dose schedule of HPV vaccination. Lessons learned from the Mexican implementation were instrumental to the recommendation by the World Health Organization of a two-dose schedule.…”
Section: Disclosurementioning
confidence: 99%
“…One local investigation in Brazil alone, the Ludwig-McGill Cohort Study, 11 generated 25 master's and doctoral theses, as well as research content for a few post-doctoral fellows. The ongoing FRIDA study 6 in Tlaxcala, Mexico, is another example where the frontlines of field research become indistinguishable from academia. Many graduate students have learned practical lessons and earned their degrees based on this study alone and many more will benefit as more data are added to this vast epidemiologic resource.…”
mentioning
confidence: 99%
“…Documentary evidence of the effect of booster doses on HPV vaccines, as in the case of Mexican women, is of particular importance from a public health perspective and in scenarios of alternative vaccination schedules because it provides support for the application of a booster dose in those scenarios of very low vaccination coverage, including 1-dose, in areas of high cervical cancer (CC) incidence or mortality or in vaccination and screening trials with HPV testing for adult women. 15,16 One of the main limitations of the study is the lack of randomization, which might result in differential exposure to HPV. However, in Mexico, a small percent (<20%) of women are sexually active before age 16,17 and when both groups were compared month at 7, there was non-inferiority in HPV16; thus, we can infer that both groups are homogeneous in month 7.…”
Section: Hpv Tetravalent Vaccine Booster Dosementioning
confidence: 99%
“…15,16 One of the main limitations of the study is the lack of randomization, which might result in differential exposure to HPV. However, in Mexico, a small percent (<20%) of women are sexually active before age 16,17 and when both groups were compared month at 7, there was non-inferiority in HPV16; thus, we can infer that both groups are homogeneous in month 7. Besides, the prevalence of the two types of HPV in the vaccine in women younger than 34 years is less than 2.2%, 18 hus the results are unlikely to be a consequence of the response to exposure, through sexual intercourse; even if differential, the prevalence is low and would have a very small effect in GMT´s.…”
Section: Hpv Tetravalent Vaccine Booster Dosementioning
confidence: 99%